The prevalence, awareness, and treatment status of diabetic retinopathy among individuals aged 18-75 years in Hubei province in 2019 - Miaoyan SHEN; Lan ZHANG; Shuzhen ZHU; Yumeng TANG; Jingju PAN; Qian LI; Mengge ZHOU; Tianjing HE (Zhongguo gonggong weisheng)
ObjectiveTo investigate the prevalence, awareness, and treatment rates of diabetic retinopathy (DR) among individuals aged 18–75 years with diabetes mellitus in Hubei province, and to provide scientific evidence for DR prevention and control. MethodsIn 2019, a multi-stage stratified cluster random sampling method was used to select 1 708 individuals aged 18–75 years with diabetes mellitus from four survey sites in Hubei province. Questionnaires, physical measurements, laboratory tests, and fundus examinations were conducted. The prevalence, awareness, and treatment rates of DR among individuals with diabetes with different characteristics were analyzed. Multivariable logistic regression analysis was used to analyze the influencing factors of DR. ResultsAfter excluding individuals without fundus photographs or with unqualified photographs, a total of 1 489 participants were included in this study. The prevalence of DR was 12.6%, the awareness rate among individuals with DR was 13.3%, and the treatment rate was 18.5%. The awareness rate (χ2=4.207) and treatment rate (χ2=7.243) were significantly higher in urban residents than in rural residents (all P<0.05). With increasing education level, the awareness rate of DR showed a significant upward trend (χ2=3.045, P<0.05); the treatment rate of DR showed a marginally significant upward trend (χ2=2.616, P=0.053). With increasing annual household income, both the awareness rate (χ2=7.148) and treatment rate (χ2=3.228) of DR showed a significant upward trend. Individuals with diabetes who had urban employee medical insurance had higher DR awareness (χ2=11.503) and treatment rates (χ²=10.800) (all P<0.05). Multivariable logistic regression analysis showed that poor fasting blood glucose control (>7 mmol/L, Wald χ2=6.563), longer diabetes duration (≥5 years, Wald χ2=22.171), and having hypertension (Wald χ2=5.760) were associated with a higher risk of DR, while having urban employee medical insurance (Wald χ2=4.612) was associated with a lower risk of DR (all P<0.05). ConclusionsThe prevalence of DR among individuals aged 18–75 years with diabetes mellitus in Hubei province is not high, but the awareness and treatment rates are low. Prevention and control education and screening efforts should be strengthened for high-risk populations with DR, with a focus on improving the awareness and treatment rates of DR among individuals in rural areas, those with low education and income levels, and those with low medical insurance coverage.